Estudo da área líquida efetiva de chapas e cantoneiras de aço tracionadas e ligadas por parafusos - Veronez, Jane Suave (2005)
This work presents a study of the net section rupture of bolted flat plates and single angles of steel tension members capacities. The modes of failure of the tension members subjected to static loads and connected with bolts are exposed at first. After that, the mode of failure of rupture of net section is established as the center of interest. A brief report above researches about the subject is presented and the sources of design calculations used by some current specifications are indicated. Afterwards, design calculations for service ability criterion, used by current specifications for laminated, welded and cold formed steel members, are presented and the divergences between those criterions are pointed out. A comparative analysis with numeric examples with laminated and welded members is accomplished, in order to exemplify the specification prescriptions. A numeric simulation of plates with concentric connections and single angles with eccentric connections are realized by the finite element analysis (FEA), in the program Ansys 5.5. After the presentation of the results, procedures to calculate the resistance of the studied models are proposed, and a comparative analysis between the results obtained on the numeric simulation and on the design calculations for service ability criterion is realized, showing the differences between them and indicating the ones that have more approximation with numeric results.